Avaliação da sustentabilidade de veículos elétricos no Brasil - Caldeira, Karlla Beatriz Miranda (Universidade Federal de São Carlos, 2024)
Amid the current climate crisis and the need to reduce environmental impacts, electric vehicles (EVs) have gained market traction, promoted as a sustainable solution for reducing greenhouse gas emissions and saving on fuel costs. However, the mere use of electricity does not, by itself, guarantee a reduction in CO2 emissions, making it essential to consider the source of this energy, particularly in a global context where the energy matrix is predominantly based on fossil fuels, such as oil and coal. This study aims to critically analyze the feasibility of electrifying the national fleet, considering economic, social, and environmental pillars. The analysis is based on the average distance traveled by Brazilians, using the bottom-up method to estimate environmental impacts and the ecological footprint. Additionally, a case study was conducted, where the feasibility of replacing a vehicle fleet of a metallurgical company in the interior of São Paulo state was evaluated based on real data on annual distance traveled and fuel costs. The study reveals that in Brazil, due to its predominantly renewable energy matrix, the switch to EVs could result in up to a 96.4% reduction in CO2 emissions compared to gasoline use. Economically, the adoption of EVs in the country is advantageous only when charged at home, providing up to 78% savings compared to ethanol refueling. At public charging stations, the savings are approximately 22.8%. However, the high cost of EVs still makes their acquisition unfeasible for most Brazilians, with the cheapest model in august/2024 costing the equivalent of 83 minimum wages.
Sustainability assessment of electric vehicles in Brazil
Keywords: Sustentabilidade; Meio ambiente; Combustíveis; Veículos elétricos; Sustainability; Environment; Fuels; Electric vehicles; ENGENHARIAS::ENGENHARIA QUIMICA